181k views
2 votes
# Expand (2x - 3)2. If a, b, and c represent

the coefficients of the resulting polynomial in

descending powers of x, what is a+b+c?

User Opsocket
by
6.0k points

1 Answer

5 votes

Answer:

a + b + c = 1

Explanation:

To expand the bracket,
(2x - 3)^(2) we will simply be multiplying the bracket by itself.

This will be the same as having
(2x - 3) * (2x - 3)

The first step in doing this is to multiply each of the values in the second bracket by the values in the first one.


2x * 2x =4x^2


2x* -3 = -6x


-3 * 2x = -6x


-3 * -3 =9

Once this is done, the next step is to group the like terms and evaluate the result.


4x^2 -6x-6x +9


4x^2 -12x +9

This is algebraic expression is the result of the expansion of
(2x - 3)^(2) .

Based on the descending powers of x

a = 4

b = -12

c = 9

These are the coefficients of
x^2 and
x and also the last figure.

a + b + c = 4 -12 +9 = 1

User Abdulla Sirajudeen
by
6.1k points